Thermochemical Properties and Dehydrogenation Thermodynamics of Indole Derivates - Konnova, Maria E.; Li, Shao; Bösmann, Andreas; Müller, Karsten; Wasserscheid, Peter; Andreeva, Irina V.; Turovtzev, V. V.; Zaitsau, Dzmitry H.; Pimerzin, Aleksey A.; Verevkin, Sergey P. (Industrial & Engineering Chemistry Research, 2020)
Indole and methylindole are heterocyclic aromatics, which can be hydrogenated and used for hydrogen storage. A huge advantage of heterocyclic components compared to homocyclic aromatics is the lower enthalpy of reaction for hydrogen release by dehydrogenation. In this study, thermochemical properties of indole and 2-methylindole and its partially and fully hydrogenated derivatives have been determined. Hydrogenation of indoles is a two-step reaction, which is highly influenced by reaction thermodynamics. High precision combustion calorimetry was used to measure enthalpies of formation of indole derivatives. The gas-phase enthalpies of formation were derived with the help of vapor pressure measurements. The high-level quantum-chemical methods were used to establish consistency of the experimental data. The standard molar thermodynamic functions of formation (enthalpy, entropy, and Gibbs energy) of indole derivatives were derived. The results showed that the partially hydrogenated species, 2-methylindoline, tends to dehydrogenate easily under hydrogen release conditions. Thus, indoline is only expected in trace amounts in the respective reaction mixture.
CRIS-Team Scopus Importer:2020-12-04